2022
DOI: 10.1097/md.0000000000029260
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of osteoporosis prevention behaviors in women in their 20s and 30s

Abstract: There is a need to provide insight into the management and health care fields for the prevention of osteoporosis in young women by analyzing the factors affecting the prevention of osteoporosis. This descriptive survey aimed to identify the predictors of osteoporosis prevention behaviors in women in their 20s and 30s by examining their body mass index (BMI), weight control experience, osteoporosis knowledge, osteoporosis self-efficacy, and osteoporosis prevention behaviors. One hundred fifty participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…An increase in one grade in osteoporosis-related knowledge increased women's probability of practicing high OPB by 1.6 times. In the same line as the present study, Kang and Kim tried to explore the predictors of OPB among women in their 20 s and 30 s. They elaborated that women with higher osteoporosis-related knowledge had significantly higher healthy behaviors and had at least one weight control experience [36]. Moreover, Rastgoo et al conducted a study to investigate the predictors of OPB among adolescents and found an indirect effect of knowledge on OPB via the intermediary roles of attitudes and behavioral intention [37].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…An increase in one grade in osteoporosis-related knowledge increased women's probability of practicing high OPB by 1.6 times. In the same line as the present study, Kang and Kim tried to explore the predictors of OPB among women in their 20 s and 30 s. They elaborated that women with higher osteoporosis-related knowledge had significantly higher healthy behaviors and had at least one weight control experience [36]. Moreover, Rastgoo et al conducted a study to investigate the predictors of OPB among adolescents and found an indirect effect of knowledge on OPB via the intermediary roles of attitudes and behavioral intention [37].…”
Section: Discussionmentioning
confidence: 82%
“…In addition, the total health belief scores were significantly associated with high OPB; therefore, they further recommended that using HBM as a framework for osteoporosis public awareness programs may be an effective intervention to change and promote OPB [43]. In addition, Self-efficacy and health motivation were found to be the most important motivators for OPB, mainly physical activities, in many studies [36,44]. Moreover, an Iranian study found a significant association between walking behaviors and the perceived susceptibility to osteoporosis and health motivation.…”
Section: Discussionmentioning
confidence: 99%